PERBANDINGAN KEMAMPUAN BERHITUNG ANTARA SISWA YANG BERASAL DARI TK DAN NON TK DI SEKOLAH DASAR INPRES 109 KOTA SORONG - Rertno Dwi Pratiwi; Mulyono Mulyono; Komayanti Komayanti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2021)
The research aims to determine: 1) numeracy skills in students from kindergarten; 2) numeracy skills in non-kindergarten students, and 3) comparison of numeracy skills in students from kindergarten and non-kindergarten. This study uses a quantitative approach with a survey research type with a population of 84 students. Sampling using saturated sampling by making the entire population the research sample. Data was collected by giving test questions. The results showed that: 1) the numeracy skills of kindergarten graduate students were in the high category (68%); 2) the ability to count in non-kindergarten students is in the high category (60%); 3) there is a difference in numeracy skills between kindergarten and non-kindergarten graduate students. Kindergarten education is recommended before entering elementary school so that students' ability to understand numbers can be more mature.